2011
DOI: 10.1111/j.1365-2036.2011.04723.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between the presence of brown adipose tissue and non‐alcoholic fatty liver disease in adult humans

Abstract: SUMMARY BackgroundThe presence of active brown adipose tissue (BAT) has been associated with a reduced risk of obesity in adult humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 24 publications
4
39
0
Order By: Relevance
“…It is well known that NAFLD is the most common form of chronic liver disease and the most common cause of elevated levels of liver enzymes in healthy individuals [25]. Considering the inverse relationship between the presence of ABAT and NAFLD, our results indicating an association between the presence of ABAT and decreased levels of ALT and AST are consistent with previous reports [5,25].…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…It is well known that NAFLD is the most common form of chronic liver disease and the most common cause of elevated levels of liver enzymes in healthy individuals [25]. Considering the inverse relationship between the presence of ABAT and NAFLD, our results indicating an association between the presence of ABAT and decreased levels of ALT and AST are consistent with previous reports [5,25].…”
Section: Discussionsupporting
confidence: 95%
“…It includes a wide spectrum of liver damage, ranging from simple steatosis to steatohepatitis, advanced fibrosis, and cirrhosis. Recently, Yilmaz et al showed an inverse correlation between the presence of ABAT and the prevalence of NAFLD on CT scans in their study including 30 ABAT(+) subjects [5]. Our results were in agreement with those of Yilmaz et al, indicating a direct correlation between the absence of ABAT and the incidence of NAFLD.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Insufficient activity of this tissue can play a role in collective pathogenesis of intra-liver triglyceride. In other words, a decrease in brown adipose tissue can increase the risk of NAFLD (48).…”
Section: Discussionmentioning
confidence: 99%